1999
DOI: 10.1523/jneurosci.19-24-10985.1999
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine-Deficient Mice Have Increased Susceptibility to Seizure-Inducing Stimuli

Abstract: Several lines of evidence suggest that norepinephrine (NE) can modulate seizure activity. However, the experimental methods used in the past cannot exclude the possible role of other neurotransmitters coreleased with NE from noradrenergic terminals. We have assessed the seizure susceptibility of genetically engineered mice that lack NE. Seizure susceptibility was determined in the dopamine ␤-hydroxylase null mutant (Dbh Ϫ/Ϫ) mouse using four different convulsant stimuli: 2,2,2-trifluroethyl ether (flurothyl), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 68 publications
7
85
0
1
Order By: Relevance
“…Because NE is required for embryonic development, we pharmacologically rescue Dbh −/− mice during gestation, but they lack NE starting at birth. Our results presented here indicate that these postnatal changes can still occur in the absence of NE.Administration of DOPS partially restores brain NE levels and reverses most of the known Dbh −/− phenotypes Palmiter, 1997, 1998;Szot et al, 1999;Weinshenker et al, 2000;Murchison et al, 2004). We have previously shown that NE transporter expression is normal in Dbh −/− mice , and our current study indicates that normal LC neuron firing and α-2 autoreceptor function are also preserved.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…Because NE is required for embryonic development, we pharmacologically rescue Dbh −/− mice during gestation, but they lack NE starting at birth. Our results presented here indicate that these postnatal changes can still occur in the absence of NE.Administration of DOPS partially restores brain NE levels and reverses most of the known Dbh −/− phenotypes Palmiter, 1997, 1998;Szot et al, 1999;Weinshenker et al, 2000;Murchison et al, 2004). We have previously shown that NE transporter expression is normal in Dbh −/− mice , and our current study indicates that normal LC neuron firing and α-2 autoreceptor function are also preserved.…”
supporting
confidence: 71%
“…NE neurons are intact and make proper connections in Dbh −/− mice, and receptor levels and co-transmitter expression are remarkably normal (Weinshenker et al, 2002b;Jin et al, 2004; Sanders et al, in press; D. Weinshenker unpublished observations). Many Dbh −/− phenotypes are reversible by acute pharamcological restoration of NE, indicating that the phenotypes are specifically due to NE deficiency (Thomas and Palmiter., 1997b;Szot et al, 1999;Weinshenker et al, 2000). However, it is unclear whether NE replacement truly restores the NE system to a "wild-type" state.…”
Section: Nih Public Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that METH-induced glutamate release in limbic brain regions may reach the threshold to trigger convulsive seizures in the absence of endogenous NE. In fact, METH is a powerful glutamate releaser [67-69], while NE is considered to be a pivotal endogenous seizure suppressive mechanism [20, 140-143]. …”
Section: The Role Of Ne In Methamphetamine-induced Behavioural Changesmentioning
confidence: 99%